Condiciones esenciales para el crecimiento de la cultura según T.S. Eliot - Ospina Garcés, Helena (2015)
This paper intends to find out in TS Eliot’s essay, Notes Towards the Definition of Culture, his concept of culture and the importance of cultural studies in language teaching and the development of modern society. T. S. Eliot wants to know whether “essential conditions” for the growth and survival of culture do exist. For Eliot, the interaction between the culture of the “individual, group, and society” is fundamental. In this framework of ideas I will share the experience of two Modern Languages School projects: Encuentro Mesoamericano “Escritura-Cultura” (ED-2080), whichhas reflected since 2006 on the interaction between “individual-group-society”, considering the centrality of the human person as the basis of an authentic culture and development. And Literary Research works in modern languages (English, German, French, Italian) (No. 23-B3-194), which has been approaching since 2013 literary criticism from an axiological and personalistic point of view.